Controlling Polymer Morphologies by Intramolecular and Intermolecular Dynamic Covalent Iron(III)/Catechol Complexation—From Polypeptide Single Chain Nanoparticles to Hydrogels. Issue 12 (13th September 2021) - Hebel, Marco; Gačanin, Jasmina; Lückerath, Thorsten; Ng, David Y. W.; Weil, Tanja
Abstract: Responsive biomaterials, tunable from the molecular to the macroscopic scale, are attractive for various applications in nanotechnology. Herein, a long polypeptide chain derived from the abundant serum protein human serum albumin is cross‐linked by dynamic‐coordinative iron(III)/catechol bonds. By tuning the binding stoichiometry and the pH, reversible intramolecular folding into polypeptide nanoparticles with controllable sizes is achieved. Moreover, upon varying the stoichiometry, intermolecular cross‐links become predominant yielding smart and tunable macroscopic protein hydrogels. By adjusting the intra‐ and intermolecular interactions, biocompatible and biodegradable materials are formed with varying morphologies and dimensions covering several lengths scales featuring rapid gelation without toxic reagents, fast and autonomous self‐healing, tunable mechanical properties, and high adaptability to local environmental conditions. Such material characteristics can be particularly attractive for tissue engineering approaches to recreate soft tissues matrices with highly customizable features in a fast and simple fashion. Abstract : Responsive biomaterials, tunable at the nanometer and macroscopic scales, are attractive for nanotechnology and tissue engineering. By adjusting the intra‐ and intermolecular interactions, a polypeptide chain derived from human serum albumin is cross‐linked by dynamic‐coordinative iron(III)/catechol complexation. The extent of cross‐linking and pH dictates whether the polypeptide folds into responsive nanoparticles or into self‐healing hydrogels.